Between Luxury and Necessity: a Socioeconomic Evaluation of Animal Protein Demand Elasticity in North Sumatra - Nababan, Selsa Juita; Ayu, Sri Fajar (Universitas Pattimura, 2025)
This study evaluates the demand elasticity of animal protein in North Sumatra Province, focusing on the relationship between price, income, and consumption patterns across four major commodities: beef, chicken, fish, and eggs. North Sumatra was purposively selected due to its status as the most populous province in Sumatra and its significant contribution to regional protein demand. The study utilizes secondary time-series data from Q1 2014 to Q4 2024, obtained from official government sources. The Linear Approximation Almost Ideal Demand System (LA/AIDS) model is applied to estimate price elasticity, income elasticity, and substitution-complementarity relationships among commodities. The results indicate that beef and chicken are price-elastic, while fish and eggs are price-inelastic. The strongest substitution effect is observed between beef and chicken. In terms of income elasticity, beef and chicken are considered luxury goods, whereas fish and eggs are classified as normal goods. These findings highlight segmented consumption patterns driven by purchasing power disparities. The study’s novelty lies in its long-term elasticity mapping of animal protein demand in a densely populated, non-Java province. Policy recommendations include price stabilization for beef and chicken, and targeted food assistance or subsidies for low-to-middle-income households to improve equitable access to quality protein. The findings enrich social science and humanities literature, particularly in food economics, public policy, and region-based food security studies.